Intestinal Barrier Breakdown and Mucosal Microbiota Disturbance in Neuromyelitis Optical Spectrum Disorders - Chunping Cui; Sha Tan; Li Tao; Junli Gong; Junli Gong; Yanyu Chang; Yuge Wang; Ping Fan; Dan He; Yiwen Ruan; Yiwen Ruan; Wei Qiu (Frontiers in Immunology, 2020)
Background and PurposeThe mechanism underlying the pathology of neuromyelitis optica spectrum disorders (NMOSD) remains unclear even though antibodies to the water channel protein aquaporin-4 (AQP4) on astrocytes play important roles. Our previous study showed that dysbiosis occurred in the fecal microbiota of NMOSD patients. In this study, we further investigated whether the intestinal barrier and mucosal flora balance are also interrupted in NMOSD patients.MethodsSigmoid mucosal biopsies were collected by endoscopy from six patients with NMOSD and compared with samples from five healthy control (HC) individuals. These samples were processed for electron microscopy and immunohistochemistry to investigate changes in ultrastructure and in the number and size of intestinal inflammatory cells. Changes in mucosal flora were also analyzed by high-throughput 16S ribosomal RNA gene amplicon sequencing.ResultsThe results from bacterial rRNA gene sequencing showed that bacterial diversity was decreased, but Streptococcus and Granulicatella were abundant in the colonic mucosa specimens of NMOSD patients compared to the HC individuals. The intercellular space between epithelia of the colonic mucosa was wider in NMOSD patients compared to the HC subjects (p < 0.01), and the expression of tight junction proteins [occludin, claudin-1 and zonula occludens-1 (ZO-1)] in NMOSD patients significantly decreased compared to that in the HC subjects. We also found numerous activated macrophages with many inclusions within the cytoplasm, mast cells with many particles in their cytoplasm, and enlarged plasma cells with rich developed rough endoplasmic reticulum in the lamina propria of the mucosa of the patients with NMOSD. Quantitative analysis showed that the percentages of small CD38+ and CD138+ cells (plasma cells) were lower, but the percentage of larger plasma cells was higher in NMOSD patients.ConclusionThe present study demonstrated that the intestinal barrier was disrupted in the patients with NMOSD, accompanied by dysbiosis and inflammatory activation of the gut. The mucosal microbiota imbalance and inflammatory responses might allow pathogens to cross the damaged intestinal barrier and participate in pathological process in NMOSD. However, further study on the pathological mechanism of NMOSD underlying gut dysbiosis is warranted in the future.